DFT based assay for tailor-made terpyridine ligand-metal complexation properties - Joshi, Krati; Krishnamurty, Sailaja; Singh, Iksha; Selvaraj, Kaliaperumal (Molecular Simulations, 2016)
Electron-rich terpyridine ligand and its metal complexes have a potential to grow as responsive surfaces by adapting their physicochemical properties as a function of environment. The responsiveness is brought about by judicious molecular level designing that is currently hindered due to lack of information and control on terpyridine (TPy)-metal (M) interactions at single molecule level. So far there is no organised understanding on the binding of different metals with TPy ligand and ways to modulate it. Being a large conjugated [GRAPHICS] system, TPy has a large scope to be functionalised with electron exchanging groups to alter its electronic structure and consequently its binding with metal atoms. In first report of such a kind, using density functional theory (DFT), we demonstrate that convenient modulation of TPy-M binding is possible through functionalisation of TPy for [GRAPHICS] , Ru, Fe, Mo and Au. Electron donating groups viz., CH [GRAPHICS] , OCH [GRAPHICS] , C [GRAPHICS] H [GRAPHICS] , NH [GRAPHICS] and electron withdrawing groups viz., CF [GRAPHICS] , COOH, CN and NO [GRAPHICS] are considered for functionalisation of TPy ligand. Significantly, the present work focuses on the functionalisation at 4 and 4 [GRAPHICS] positions of TPy molecule. The role of such a functionalisation in influencing the ligands structure-property correlation is missing in the literature to the best of our knowledge. The present investigation quantifies that by pertinent functionalisation of TPy, TPy-M binding energies can be modified up to [GRAPHICS] 60kcal/mol. Our results reveal that functionalisation leads to a considerable charge redistribution within the TPy-M complex with carbon atoms in pyridine rings functioning as major electron sink/source with a corresponding red/blue shift of [GRAPHICS] stretching frequency. This modifies the red-ox, optical and other chemical properties of TPy-M complexes. In brief, the present report illustrates a way to design ligands such as TPy for diverse applications through tailor-made functionalisation using electronic structure methodology.
Keywords: Binding energy; charge redistribution; Density functional theory; functionalisation; Metal organic complexes; metal-ligand interactions; terpyridine

Au26: a case of fluxionality/co-existence - Joshi, Krati; Krishnamurty, Sailaja (Physical Chemistry Chemical Physics, 2018)
The Au26 cluster is one of the widely studied gold clusters in the size range of n = 21–30. It has been proposed in a more recent combined experimental and theoretical study that the neutral Au26 cluster is fluxional. The fluxionality of a cluster is relevant to its catalytic applications. In this context, to explore the extent of fluxionality, Born Oppenheimer Molecular Dynamical (BOMD) simulations are carried out on experimentally and theoretically proposed fluxional Au26 conformations (three compact or core–shell structures and a high symmetry cage structure). The simulations reveal that the high energy golden tube outperforms the ground state structure (compact C2v conformation) as well as the other two low-symmetry compact conformations in terms of thermal stability. The enhancement in the thermal stability is explained on the basis of structural integrity imposed by the open skeleton of shortest bond distances within Au26-Tube. In addition to this, the homogeneous distribution of charges and the strong s–d hybridization exhibited by FMOs are seen to play a pivotal role in increasing the stability of Au26-Tube. The present investigation also reveals that the characteristic fluxionality proposed to exist in the Au26 system is noted only above 400 K and it is missing at room temperature. The simulations also bring forth the question of how relevant a ground state conformation is at working temperatures.

Probing the catalytic activity of pristine and doped Pd and Ni metal clusters towards H2O molecule - Samal, Pragnya Paramita; Joshi, Krati; Kaliaperumal, Selvaraj; Krishnamurty, Sailaja (Computational and Theoretical Chemistry, 2019)
Electrolysis of H2O to produce molecular hydrogen, the most environment friendly and energy efficient fuel, using cost effective catalysts is one of the major global research challenges. To date, Pt remains the best suitable and yet highly expensive electro-catalyst for hydrogen evolution reaction. Design of an alternative cost-effective catalyst requires a fundamental molecular level understanding of the water molecule adsorption and its activation. In that context, we examine the adsorption and activation of water molecule on model alternative catalysts namely, Ni-6 and Pd-6 clusters using density functional theory based methodology. Ni-6 and Pd-6 clusters and their singly doped counterparts are used for this study. Mo, W, Fe, Co and Cu are used as doping elements. To quantify the influence of medium (neutral and alkaline) on the activation of the water molecule, Ni based clusters are considered in neutral and anionic states, respectively. The activity of these clusters towards H2O molecule is evaluated in terms of the adsorption energy, charge transfer, bandgap, red shift in O-H stretching frequency and dissociation barriers for H2O. The studies demonstrate that doping with Co in all the studied clusters (Pd-6, Ni-6 and anionic Ni-6) increases their activity. Best activity is noted for Fe doped neutral Ni b clusters with a dissociation barrier of 5.76 kcal/mol.
Keywords: Activation barrier; Ni clusters; O-H activation; Pd clusters; Red shift of O-H stretching frequency; Water adsorption

Role of structural distortion in stabilizing electrosynthesized blue emitting phosphorene quantum dots - Valappil, Manila Ozhukil; Joshi, Krati; John, Lisa; Krishnamurthy, Sailaja; Jana, Bikash; Patra, Amitava; Pillai, Vijayamohanan K.; Alwarappan, Subbiah (Journal of Physical Chemistry Letters, 2019)
Luminescent phosphorene quantum dots (PQDs) have emerged as fascinating nanomaterials for potential applications in optoelectronics, catalysis, and sensing. Herein, we investigate the structural distortion of black phosphorus (BP) under an applied electric field to yield blue luminescent PQDs [average diameter 8 +/- 1.5 nm (N = 60)]. The electrosynthesized PQDs exhibit photoluminescence emission independent of excitation wavelength with 84% quantum efficiency. Structural distortion that occurred during the transformation of BP to PQDs is confirmed by results obtained during transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. Further, using first-principles-based density functional theory, calculations on oxygenated and nonoxygenated PQDs augment the experimental observations that an optimum oxygen content maintains the structural integrity of PQDs, above which the structural robustness of PQDs is drastically diminished.

Surface functionalization: an efficient alternative for promoting the catalytic activity of closed shell gold clusters - Joshi, Krati; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Physical Chemistry Chemical Physics, 2020)
{Surface functionalization through adsorption of ligands or non-metal atoms is considered to be an interesting and viable approach for tuning the physicochemical properties of gold clusters. Highly stable and magic numbered electronic configurations of thiolate protected gold clusters such as Au-25(SR)(18), Au-38(SR)(24)etc. with intriguing properties are the direct manifestation of the rich chemistry of the Au-S interface. The present investigation discerns the CO oxidation activity of structurally well characterized sulphur functionalized gold cluster anions AumS4-

Unravelling the distinct surface interactions of modified graphene nanostructures with methylene blue dye through experimental and computational approaches - Manappadan, Zinoy; Kumar, Shubham; Joshi, Krati; Govindaraja, Thillai; Krishnamurty, Sailaja; Selvaraj, Kaliaperumal (Journal of Hazardous Materials, 2020)
Nanoscopic modifications leading to multi-dimensional graphene structures are known to significantly influence their candidature for several applications including catalysis, energy storage, molecular sensing and most significantly adsorption and remediation of harmful materials such as dyes. The present work attempts to identify the key trajectories that connect the structural qualification with a chosen application, viz., the interactive forces in dye remediation. Various physico-chemically Modified Graphene Nanostructures (MGNs) such as 2 dimensional Graphite, Graphene Oxide (GO), reduced GO (rGO), holey rGO, and 3 dimensional GO hydrogel and Holey GO hydrogel are chosen and synthesised herein. These represent varieties of physicochemical features with respect to their dimensionality, surface features such as oxygen functionality, nanoscopic holes etc., that contribute to their characteristic overall surface interactions. Methylene Blue (MB), a popular industrial effluent posing major environmental concern is chosen to be a probe adsorbate in this case study. An exclusive real time in-situ UV visible spectral experiment provides the revealing reasons behind the outstanding performance of 2D GO sheets with an adsorption capacity of greater than 92 % even at high MB concentrations (>2000 ppm). A complex dependency of various factors such as surface oxygen, morphology, nanoporosity etc. on the unique overall interaction with an adsorbent such as MB by all these adsorbates is demonstrated using experimental and DFT based computational studies. Electrostatics and hydrogen bonding are understood to be the two dominant forces driving the MB adsorption on the best performing GO here.
Keywords: Density functional theory; In-situ UV-vis spectroscopy; Interactions; Methylene blue; Modified Graphene Nanostructures

Exploring edge functionalised blue phosphorene nanoribbons as novel photocatalysts for water splitting - Maibam, Ashakiran; Chakraborty, Debalina; Joshi, Krati; Krishnamurty, Sailaja (New Journal of Chemistry, 2021)
Hydrogen gas, a highly combustible and eco-friendly fuel is stealing the limelight and its production is one of the major areas of research. An efficient and green method for producing clean hydrogen gas with no harmful by-product is water splitting. With the introduction of low dimensional materials, water splitting has become an easier and cost-effective process. The present work demonstrates the application of one such low dimensional material viz., edge functionalised Blue Phosphorene Nano-Ribbons (BPNRs) as potential photocatalysts. With a carrier mobility of 10(3) cm(2) V-1 s(-1) and a band gap of 1.5-3.0 eV, BPNRs are an attractive candidate for photocatalysis. BPNRs with different edge oreintations, viz. zigzag and armchair are functionalised with CH3O, COOCH3, CHO, COOH, OH, NH2, CONH2, SH, C6H5, and NO2 groups. Their performance towards activating water molecules at different sites on the nanoribbon is studied. The functionalised edges of the BPNRs are the active sites showing similar to 1.2% to 3.2% efficiency in activating the O-H bond of the water molecule. Among the different groups explored, CONH2 functionalised zigzag BPNR clearly exhibits a higher potential towards the adsorption of water molecules (-0.98 eV) and activation of O-H bonds with an elongation of 3.2% and a red shift of 500.6 cm(-1). This is attributed to the lone pair of electrons on the nitrogen atom contributing to the electron donating nature of the CONH2 functional group.

Finite temperature behavior of carbon atom-doped silicon clusters: depressed thermal stabilities, coexisting isomers, reversible dynamical pathways and fragmentation channels - Joshi, Krati; Maibam, Ashakiran; Krishnamurty, Sailaja (New Journal of Chemistry, 2021)
Silicon carbide clusters are significant due to their predominant occurrence in meteoric star dust, particularly in carbon-rich asymptotic giant branch stars. Of late, they have also been recognized as nanoclusters with potential applications in technology. Them both being elements of the same group, there is excellent potential for precise control over the physico-chemical properties of such molecular length-scale materials through atomic engineering and this has been explored recently by various experimentalists. This report simulates one of the significant physical properties, viz. conformational stability, of various carbon-doped silicon clusters as a function of temperature using Born-Oppenheimer molecular dynamics methodology. Single carbon atom-doped silicon clusters with 4-9 atoms (i.e., Si3C-Si8C) are chosen for this study as the gas phase geometries of these clusters have been characterized using a combination of experimental and theoretical methods in the recent past. The simulations ratify that various conformations do not interconvert among themselves at 300 K. The interconversion occurs at 500 K or above, thereby ratifying the possibility of the coexistence of multiple conformations of a given cluster, which are generally synthesized under subroom temperature conditions. Furthermore, the above single carbon atom-doped silicon clusters: (a) have depressed thermal stabilities as compared to their pristine counterparts with the exception of a Si5C conformation; (b) undergo multifarious evolution of the cluster, through the reversible dynamical and fragmentation pathways as a function of temperature and (c) single carbon atom-doped silicon clusters with 7 atoms (starting from Si6C) and above undergo a fragmentation at nearly 2000 K. The underlying electronic and structural properties of various clusters are discussed to explain the above observations with a note on critical fragmentation energy barriers required for the segmentation of clusters with seven or more atoms.

Quantum dot (Aun/Agn, n=3-8) capped single lipids: interactions and physicochemical properties - Maneri, Asma H. H.; Varode, Shruti Suhas; Maibam, Ashakiran; Ranjan, Priyatosh; Krishnamurty, Sailaja; Joshi, Krati (Physical Chemistry Chemical Physics, 2023)
Realizing the potential of nano-hybrid biomaterials in various applications (nanoprobes to drug delivery), special attention has been devoted towards their synthesis and development. Nonetheless, several questions pertaining to the interface chemistry between the constituent entities (biomolecules and organic/inorganic part) of these hybrids, still remain unresolved. Keeping these unsolved issues in mind, the present theoretical investigation focuses on determining the electronic/physicochemical properties and interactions within gold and silver quantum dot-capped single lipid molecules. Quantum dots of varying sizes and shapes have been chosen and then coupled with lipid molecules (1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), 1,2-dimyristoyl-sn-glycero-3-phosphoethanolamine (DMPE), 1,2-dimyristoyl-sn-glycero-3-phosphoglycerol, sodium salt (DMPG)), at the choline/glycerol, carboxylate and phosphate site. It has been identified that Au Qds interact strongly as compared to Ag clusters. In addition to the type, the shape and size of the Qd also influences their attachment with lipids. Among various sites, the phosphate site provides a considerably stronger platform for the coupling of Qds. On the other hand, attachment at the choline site leads to significantly lower interaction energies. The trend noted in interaction energies coincides with the structure-electronic property analysis (interatomic bond distances, charge transfer, PO2- stretching frequencies), which further helps in deducing the nature of interactions. The molecular dynamics simulations performed on selected Qd-lipid complexes established that the Qd interacting with lipids at the phosphate site remains fairly stable at room temperature without undergoing fragmentation into individual components. On the other hand, at the choline site, the Qd-to-lipid coupling is unstable and therefore they experience disintegration at 300 K temperature. Additionally, a unique glycerol-to-phosphate site crossover is evidenced, which reaffirms that the phosphate site is selectively preferred by Qds for binding with lipid molecules.

Understanding the stability of an unprecedented Si-Be bond within quantum confinement - Maneri, Asma Harun; Krishnamurty, Sailaja; Joshi, Krati (ACS Omega, 2023)
As of today, the Si-Be bond remains underexplored in the literature, and therefore its anomalous behavior continues to be an unsolved puzzle to date. Therefore, the present study aims at evaluating the integrity of an unprecedented Si-Be bond within quantum confinement. To accomplish this, first-principles-based calculation are performed on Be-doped silicon clusters with atomic sizes 6, 7, and 10. Silicon clusters are sequentially doped with one, two, and three Be atoms, and their thermal response is registered in the temperature range of 200-1500 K, which discloses several research findings. During the course of the simulations, the clusters face various thermal events such as solid cluster phase, rapid structural metamorphosis, and fragmentation. Si-Be nanoalloy clusters are noted to be thermally stable at lower temperatures (200-700 K); however, they begins to disintegrate earlier at a temperature as low as 800 K. This lower stability is attributed to the weak nature of Si and Be heteroatomic interactions, which is corroborated from the structural and electronic property analysis of the doped clusters. In addition to this, the performance of Be-doped clusters at finite temperatures is also compared with the thermal response of two other popular systems, viz., C-and B-doped silicon clusters.

Investigation of cathinone analogs targeting human dopamine transporter using molecular modeling - Shivankar, Bhavana R.; Bhandare, Vishwambhar Vishnu; Joshi, Krati; Patil. Vishal S.; Dhotare, Priyanka Shrikant; Sonawane, Kailas Dasharath; Krishnamurty, Sailaja (Journal of Biomolecular Structure & Dynamics, 2024)
In a step towards understanding the structure–property relationship among Synthetic Cathinones (SCs), a combined methodology based on Density Functional Theory (DFT), Administration, Distribution, Metabolism, Excretion, and Toxicity (ADMET) predictions, docking and molecular dynamics simulations have been applied to correlate physicochemical descriptors of various SCs to their biological activity. The results from DFT and molecular docking studies correlate well with each other explaining the biological activity trends of the studied SCs. Quantum mechanical descriptors viz. polarizability, electron affinity, ionization potential, chemical hardness, electronegativity, molecular electrostatic potential, and ion interaction studies unravel the distinguishingly reactive nature of Group D (pyrrolidine substituted) and Group E (methylenedioxy and pyrrolidine substituted) compounds. According to ADMET analysis, Group D and Group E molecules have a higher probability of permeating through the blood–brain barrier. Molecular docking results indicate that Phe76, Ala77, Asp79, Val152, Tyr156, Phe320, and Phe326 constitute the binding pocket residues of hDAT in which the most active ligands MDPV, MDPBP, and MDPPP are bound. Finally, to validate the derived quantum chemical descriptors and docking results, Molecular Dynamics (MD) simulations are performed with homology-modelled hDAT (human dopamine transporter). The MD simulation results revealed that the majority of SCs remain stable within the hDAT protein’s active sites via non-bonded interactions after 100 ns long simulations. The findings from DFT, ADMET analysis, molecular docking, and molecular dynamics simulation studies complement each other suggesting that pyrrolidine-substituted SCs (Group D and E), specifically, MPBP and PVN are proven potent SCs along with MDPV, validating various experimental observations.

Size and morphology dependent activity of Cu clusters for CO2 activation and reduction: a first principles investigation - Amin, Seerat; Krishnamurty, Sailaja; Dar, Manzoor Ahmad; Joshi, Krati (ChemPhysChem, 2024)
Various Cu-based materials in diverse forms have been investigated as efficient catalysts for electrochemical reduction of CO2; however, they suffer from issues such as higher over potential and poor selectivity. The activity and selectivity of CO2 electro reduction have been shown to change significantly when the surface morphology (steps, kinks, and edges) of these catalysts is altered. In light of this, size and morphology dependent activity of selected copper clusters, Cun (n=2-20) have been evaluated for the activation and reduction of CO2 molecule. The phase-space of these copper clusters is rich in conformations of distinct morphologies starting from planar, 2D geometries to prolate-shaped geometries and also high-symmetry structures. The binding efficiency and the activation of CO2 are highest for medium sized clusters (n=9-17) with prolate-morphologies as compared to small or larger sized CunCO(2) clusters that are existing mainly as planar (triangular, tetragonal etc.) or highly-symmetric geometries (icosahedron, capped-icosahedron etc.), respectively. The best performing (prolate-shaped) CunCO2 conformations are quite fluxional and also they are thermally stable, as demonstrated by the molecular dynamics simulations. Furthermore, on these CunCO(2) conformations, the step-by-step hydrogenation pathways of CO2 to produce value-added products like methanol, formic acid, and methane are exceptionally favorable and energy-efficient.
Keywords: CO2 activation; CO2 hydrogenation; Copper clusters; Density Functional Theory (DFT); molecular dynamics

Far-red active squaraine dye-sensitized photoanode for dye-sensitized solar cells with a copper (II/I) electrolyte - Nawghare, Indrajeet S.; Deshmukh, Shivdeep Suresh; Joshi, Krati; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on TiO2 and charge recombination between electrons present in TiO2 and electrolyte can be achieved by wrapping the long alkyl groups around the dye structure and further introducing bulky donor on the dye is a potential approach to enhance both the open-circuit potential and short-circuit current parameters. Additionally, bulky donor containing dye structures modulates the photophysical and electrochemical properties of the sensitizer which helps reducing the over potentials required for the dye regeneration process by utilizing a multidentate ligand containing [Cu(tme)]2+/+ and I- /I3redox electrolytes. Hagfeldt donor appended far-red NIR active unsymmetrical squaraine dye (SQ-HF) has been designed, synthesized, and characterized. SQ-HF dye showed an intense absorption at 676 nm (epsilon 1.7 x 105 M- 1cm- 1). Photophysical and electrochemical studies indicated that the LUMO and HOMO energy levels of the SQ-HF dye were suited for charge injection (from the LUMO of the dye to the conduction band of TiO2) and dyeregeneration processes, respectively. The DSSC device efficiency of 5.15 % (JSC of 10.83 mA/cm2 and VOC of 0.690 V) has been achieved for SQ-HF dye by utilizing a literature reported [Cu(tme)]2+/+ and 4.11 % (JSC of 8.74 mA/cm2 and VOC of 0.702 V) in I- /I3- redox shuttles, respectively.
Keywords: aggregation of dyes; Bulky donor; dye-sensitized solar cell; Photocurrent generation; squaraine dye

Rational design of hydrophobic Cu/CuO electrodes for electrochemical oxygenation of tetralin: a strategic approach - Cherukuthota, Sri Vidya; Mathew, Elizabeth; Verma, Tushar Singh; Joshi, Krati; Selvaraj, Kaliaperumal (ChemSusChem, 2025)
Electro-organic synthesis presents a sustainable and practical alternative to traditional organic synthesis methods, which typically utilize harsh reagents and require energy-intensive conditions. Nevertheless, the challenge of achieving satisfactory conversion and selectivity rates in electrocatalytic oxidation using a non-platinum group metal (PGM) catalyst pair still needs to be addressed. This study demonstrates the application of a non-PGM-based catalyst pair for the electrocatalytic oxidation of tetralin to 1-tetralone, a highly demanded raw material in the pharma industry. Copper electrodeposited on teflonated carbon paper combined with copper foam as the electrocatalyst pair has demonstrated impressive conversion and selectivity ratios to electro-synthesize 1-tetralone at room temperature and atmospheric pressure. The optimal choice of a non-PGM catalyst, ideal mass loading, and a unique electrode configuration resulted in an ultimate conversion of about 99% of tetralin and 1-tetralone selectivity -93.7%, yield -92.6%. The reaction pathway associated with the electrochemical phenomena is supported by first principles-based density functional theory calculations and X-ray photoelectron spectroscopy of the electrocatalyst. This process has exceptional performance that can be adapted for a wide range of substrates and is straightforward, ambient, reagent-free, scalable, and therefore beneficial for industrial use. Therefore, initiatives have been taken in this direction.
Keywords: C-H activation; Copper; electrochemical oxidation; non-PGM electrocatalysts; tetralin; Tetralone